Steric Repulsion Induced Conformational Switch in Supramolecular Structures - Senge, Mathias (My University, 2022)
Inspired by the rigidified architecture of ‘picket-fence’ systems, we propose a strategy utilizing strain to impose intramolecular tension in already peripherally overcrowded structures leading to selective atropisomeric conversion. Employing this approach, tuneable shape-persistent porphyrin conformations were acquired exhibiting distinctive supramolecular nanostructures based on the orientation of the peripheral groups. The intrinsic assemblies driven by non-covalent bonding interactions form supramolecular polymers while encapsulating small molecules in parallel channels or solvent-accessible voids. The developed molecular strain engineering methodologies combined with synthetic approaches have allowed the introduction of the pivalate units creating a highly strained molecular skeleton. Changes in the absorption spectrum indicated the presence of severe steric repulsions between the peripheral groups which were confirmed by single crystal X-ray analysis. To release the steric strain introduced by the peripheral units, thermal equilibration strategies were used to selectively convert the most abundant atropisomer to the desirable minor one.
Keywords: Atropisomerism; Nonplanar Porphyrins; Tunable Supramolecular Complexes